Peranan Pasar Modal Dalam Perekonomian Negara - Yenni Samri Juliati (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2015)
The role of the capital market as a source of funding companies that have significant implications for the country's economy is not just an alternative but has been able to become a major funding source. Funds offered in the capital market through some corporate action such as recording the initial stock (initial public offering / IPO), the listing of new shares (rights issue) as well as the issuance of bonds annually assessed far more efficient than the funding obtained from the company's bank loans. Especially when inflation trends are increasing, which indirectly affects the interest rates of bank loans. The number of companies listed IPO, rights issue or bonds as well as funds raised from the three corporate action recorded significant results in each year. Although there are fluctuations in comparison, which is influenced by the economy at home and abroad, in each year, but it did not dampen the interest of companies to keep funding in the capital markets.